HUBUNGAN PERSEPSI SISWA TENTANG KEWIBAWAAN GURU DENGAN SIKAP BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 189 PEKANBARU - Purwati, Endang; Syahrilfuddin, Syahrilfuddin; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the importance of students' perceptions about the authority of teachers that will be related to student learning attitudes. An authoritative teacher will produce good interactions with students, so the learning activities will go well. This study aims to look at the relationship between students 'perceptions about the authority of teachers with students' mathematics learning attitudes. This type of research is quantitative research with a correlation approach. The population in this study amounted to 164 students. The sample used in this study was a random sampling so that a sample of 60 people was obtained. The results of research students' perceptions of the authority of the teacher got an average percentage score of 85% with a very high category, for the attitude of learning mathematics students got an average percentage score of 85% with a very high category. Furthermore, the correlation analysis results obtained (3.081)> (1.67) then Ha is accepted and Ho is rejected, where the authority of the teacher contributes to the attitude of learning mathematics by 14.10% and the remaining 85.90% is determined by other factors and the relationship of student perception about the authority of teachers with the attitude of learning mathematics students in on class V 189 Primary School Pekanbaru Pekanbaru with a Pearson Correlation value of 0.375, which means positive with a low level of correlation.Key Words: Perception, Authority, Attitude